Sulfamic Acid: An Efficient Catalyst for the Diastereoselective, One-Pot Synthesis of Pyrano Benzopyrans, Furano Benzopyrans and Ethoxy Benzopyrans - Kumar, R. S.; Nagarajan, R.; Vijay, K.; Perumal, P. T. (Letters in Organic Chemistry, 2005)
Sulfamic acid catalyses the one-pot three components coupling of aldehydes, anilines and electron rich dienophiles such as dihydropyran, dihydrofuran and ethyl vinylether resulting in the formation of pyrano, furano and ethoxy benzopyrans.
Keywords: sulfamic acid